Role for Granulocyte Colony‐Stimulating Factor in Neutrophilic Extramedullary Myelopoiesis in a Murine Model of Systemic Juvenile Idiopathic Arthritis. Issue 7 (31st May 2022) - Malengier‐Devlies, Bert; Bernaerts, Eline; Ahmadzadeh, Kourosh; Filtjens, Jessica; Vandenhaute, Jessica; Boeckx, Bram; Burton, Oliver; De Visscher, Amber; Mitera, Tania; Berghmans, Nele; Verbeke, Geert; Liston, Adrian; et al.
Abstract : Objective: Systemic juvenile idiopathic arthritis (JIA) is a systemic inflammatory disease with childhood onset. Systemic JIA is associated with neutrophilia, including immature granulocytes, potentially driven by the growth factor granulocyte‐colony stimulating factor (G‐CSF). This study was undertaken to investigate the role of G‐CSF in the pathology of systemic JIA. Methods: Injection of Freund's complete adjuvant (CFA) in BALB/c mice induces mild inflammation and neutrophilia in wild‐type (WT) mice and a more pronounced disease, reminiscent to that of JIA patients, in interferon‐γ–knockout (IFNγ‐KO) mice. Extramedullary myelopoiesis was studied in CFA‐immunized mice by single‐cell RNA sequencing, and the effect of G‐CSF receptor (G‐CSFR) blockage on neutrophil development and systemic JIA pathology was evaluated. Additionally, plasma G‐CSF levels were measured in patients. Results: Both in systemic JIA patients and in a corresponding mouse model, plasma G‐CSF levels were increased. In the mouse model, we demonstrated that G‐CSF is responsible for the observed neutrophilia and extramedullary myelopoiesis and the induction of immature neutrophils and myeloid‐derived suppressor‐like cells. Administration of a G‐CSFR antagonizing antibody blocked the maturation and differentiation of neutrophils in CFA‐immunized mice. In IFNγ‐KO mice, treatment was associated with almost complete inhibition of arthritis due to reduced neutrophilia and osteoclast formation. Disease symptoms were ameliorated, but slight increases in interleukin‐6 (IL‐6), tumor necrosis factor, and IL‐17 were detected upon G‐CSFR inhibition in the IFNγ‐KO mice, and were associated with mild increases in weight loss, tail damage, and immature red blood cells. Conclusion: We describe the role of G‐CSF in a mouse model of systemic JIA and suggest an important role for G‐CSF–induced myelopoiesis and neutrophilia in regulating the development of arthritis.